Komunikasi Antar Budaya di Lingkungan Universitas Negeri Makassar - Nasri Indra Padang; Mr. Najamuddin; St. Junaeda (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to determine the way of intercultural communication between Bugis-Makassar and Papuan ethnic students at the Makassar State University, the perception of Papuan students on the acceptance of students from Bugis-Makassar towards themselves as a minority group, and the factors supporting the communication process between Bugis-Makassar ethnic students. and ethnic Papuans. This research is descriptive in nature, where the informants are students of ethnic Bugis-Makassar and ethnic Papuans who are registered at Makassar State University and ethnic Bugis-Makassar and ethnic Papuan communities as supporting informants. Data was collected through observation, interviews, and documentation. Data analysis techniques by means of data collection stages, data reduction stages, data display, verification and drawing conclusions. The results showed that the process of intercultural communication among Bugis-Makassar and Papuan ethnic students at the State University of Makassar can be seen from the indicators of the communicative situation, including differences in the atmosphere in receiving material and differences in the use of language during lectures. The perception of students from Papua on the acceptance of students from Bugis-Makassar towards themselves as a group with a minority number in the Makassar State University can be seen from the results of equality indicators who understand in applying cultural tolerance or respect for one another. The supporting actors in the communication process between Bugis-Makassar and ethnic students are seen from the indicators of openness, empathy, positive feeling and support.